GOOD GOVERNANCE DALAM PENGELOLAAN PEMBIAYAAN PENDIDIKAN PADA ERA SOCIETY 5.0 - Akhmad Fadholi; Sarki Sarki; Sutrisno Sutrisno (Dharmas Education Journal (DE_Journal), 2026)
Education financing management in the Society 5.0 era requires the implementation of transparent, accountable, effective, and technology-based governance. This study aims to analyze the implementation of Good Governance in education financing management and identify the role of digitalization in improving the quality of modern educational governance. The study employed a qualitative approach using a library research method. Data were collected through the review of national and international journal articles, books, proceedings, and other scientific documents relevant to the research topic. Data analysis was conducted using content analysis through data reduction, theme classification, interpretation, and conclusion drawing. The findings reveal that the principles of transparency, accountability, effectiveness, efficiency, and participation play an essential role in creating professional and sustainable education financing management. The integration of digital technology through educational financial information systems improves the quality of financial administration, strengthens budget supervision, and supports data-based decision making. The implementation of digital-based Good Governance also contributes to increasing public trust and improving the quality of educational services. However, challenges remain in terms of human resource competence, organizational transparency culture, and technological infrastructure limitations. This study implies that strengthening digital-based education financing governance is an important strategy in supporting educational transformation in the Society 5.0 era..